Validity and reliability of a questionnaire on the knowledge, attitudes, perceptions and practices toward food poisoning among Malaysian secondary school students: a pilot study - Ramu, Pawitra; Osman, Malina; Abdul Mutalib, Noor Azira; Aljaberi, Musheer A.; Lee, Kuo-Hsin; Lin, Chung-Ying; Hamat, Rukman Awang (MDPI, 2023)
Children in school settings are at risk of contracting food poisoning due to inadequate food safety practices and safe eating behaviors. This research aimed to develop a valid and reliable questionnaire on the knowledge, attitudes, perceptions, and practices (KAP2) toward food poisoning and its prevention among secondary school students. The questionnaire was developed by considering the Health Belief Model (HBM). A pilot study using a cross-sectional survey was conducted in Tangkak, Johor, among 30 selected students using a convenience sampling method. A pre-test was conducted on 15 secondary school students aged 13–17 years old prior to the pilot study, and they were excluded from the pilot study. The constructed knowledge was assessed using the difficulty and discrimination indices. Meanwhile, the reliability of the attitude, practice, and perception components in the questionnaire were assessed using Cronbach’s alpha. Regarding knowledge (34 items), the difficulty index showed that most items (n = 28) were easy, while one was difficult, and the remaining five were within an acceptable range. In addition, the discrimination index of the knowledge component (34 items) showed that twenty-two, three, and one had good, acceptable, and excellent ranges, respectively. Only eight items had a low discrimination power. All items of the attitude and practice components (10 items for each) showed a corrected item-total correlation value of >0.30. Only four out of twenty-one items of the perception component showed an unacceptable range of <0.30. However, following a discussion with the experts, all items were retained. With the incorporation of the HBM, the 75-item adapted food poisoning KAP2 questionnaire is valid and reliable. It can be utilized to measure and generate food poisoning KAP2 among secondary school students in Malaysia.